The Importance of Certification of Business Process Modelling Competencies - Marek SZELAGOWSKI; Justyna BERNIAK-WOZNY; Piotr BIERNACKI (Communications of International Proceedings, 2021)
Process management requires a holistic view of the organization. Its practical implementation requires a coherent combination of management philosophy, methods, and tools. This requires the harmonious combination of knowledge, skills, and social competences, as well as the ability to learn, as the concept of process management itself and its methodology and tools are constantly being adapted to the changing requirements of business. The basis for communication in teams implementing and using process management is a common language (notation) of process description. Therefore, in 2014 the Systems Research Institute of the Polish Academy of Sciences decided to create the Polish BPMN Certificate. Its purpose is to reliably confirm BPMN knowledge by an independent institution. The aim of the article is to present a summary of the organization's needs in the field of certification, resulting from previous experience, and the extension of the Process Competencies Certification Program (PCCP). In the first part, the article summarizes previous experience and certification needs from various points of view (administration and business; knowledge managers and employees; educational institutions and system vendors supporting process management). Then, it discusses and summarizes the experience of certification programs in the area of process management and other areas such as project management, human resources management, or finance. In the third part, the article presents the concept of the Process Competencies Certification Program, developed on the basis of the above-mentioned analyses, which integrates the development of knowledge workers and increases the process maturity of an organization.
Keywords: BPM; Polish BPMN Certificate; Process Competencies Certification Program (PCCP).